2005
DOI: 10.1080/15376520590968833
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Essential Oils and Monolaurin onStaphylococcus aureus:In VitroandIn VivoStudies

Abstract: The antimicrobial properties of volatile aromatic oils and medium-chain fatty acids derived from edible plants have been recognized since antiquity. To give examples, Origanum oil, used as a food-flavoring agent, possesses a broad spectrum of antimicrobial activity due, at least in part, to its high content of phenolic derivatives such as carvacrol and thymol. Similarly, lauric acid, present in heavy concentrations in coconuts, forms monolaurin in the body that can inhibit the growth of pathogenic microbes. Us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 28 publications
0
26
0
1
Order By: Relevance
“…Preuss et al carried out experiments to test the antimicrobial activity of carvacrol bearing essential oils for the therapy of S. aureus infections [71]. Kristinsson et al [72] showed that the vapors of Ocimum basilicum essential oil and its components (carvacrol, thymol, salicylaldehyde) placed in the ear canal of rats with experimental acute otits media caused by pneumococci or Hemophilus influenza, can effectively treat this pathology.…”
Section: In Vivo Studiesmentioning
confidence: 98%
“…Preuss et al carried out experiments to test the antimicrobial activity of carvacrol bearing essential oils for the therapy of S. aureus infections [71]. Kristinsson et al [72] showed that the vapors of Ocimum basilicum essential oil and its components (carvacrol, thymol, salicylaldehyde) placed in the ear canal of rats with experimental acute otits media caused by pneumococci or Hemophilus influenza, can effectively treat this pathology.…”
Section: In Vivo Studiesmentioning
confidence: 98%
“…Origanum oil, used as food-flavouring agent, possesses a broad spectrum of antimicrobial activity due, at least in part, to its high content of phenolic derivatives, such as carvacrol and thymol (Preuss et al, 2005) In the literature, there are many reports relating the chemical composition and the antimicrobial properties of the essential oils of various origanum species, and their application in various commercial preparations, as antimicrobials and antioxidants (Baydar, Sagdic, Ozkan, & Karadogan, 2004;Kulisic, Radonic, Katalinic, & Milos, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…15 Glycerol monolaurate is generally recognized as safe for human use by Food and Drug Administration, and this compound is commonly used in the cosmetic and food industries. 16,17 Unlike most antibiotics that have single targets for antibacterial activity, monolaurin appears to target nonspecifically many signal transduction systems present at bacterial surface through interactions with plasma membranes.…”
Section: Introductionmentioning
confidence: 99%